(3ebOeI aj Yde GdEOGQI (B/s - (3JGjdhQ GdKGdK, HQfGQOs ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2007)
(3jVe Yde GdGOGQI, GdHQeLI GdNWjI UjGZI GdfehPL hGdMd GdHjGfj, GdHQeLI GdNWjI Md GdMGSH hJMdjd GdMSGSjI, GdHQeLI GdNWjI CeKdI dHfGA GdfeGPL, GdHQeLI ZjQ GdcSQjI, eTGcd Gdfbd hfbd GdTMfGJ hGdJNUjU, feGPL JOab GdTHcGJ, GOGQI GdTQhY, GJNGP GdbQGQ eJYOO GdeYGjjQ, GdHQeLI ZjQ GdNWjI(B. s
(3edGMb U(B.1043s
Keywords: (3GdGOGQIs; (3GdHQeLI GdNWjIs; (3OQGSI GdLOhis